The CAGE–MiR-181b-5p–S1PR1 Axis Regulates Anticancer Drug Resistance and Autophagy in Gastric Cancer Cells - Yeon, Minjeong; Kim, Youngmi; Pathak, Deepak; Kwon, Eunju; Kim, Dong Young; Jeong, Myeong Seon; Jung, Hyun Suk; Jeoung, Dooil (Frontiers in Cell and Developmental Biology, 2021)
Cancer-associated gene (CAGE), a cancer/testis antigen, has been known to promote anticancer drug resistance. Since the underlying mechanisms of CAGE-promoted anticancer drug resistance are poorly understood, we established Anticancer drug-resistant gastric cancer cells (AGSR) to better elucidate possible mechanisms. AGSR showed an increased expression level of CAGE and autophagic flux compared with anticancer drug-sensitive parental gastric cancer cells (AGS cells). AGSR cells showed higher invasion potential, growth rate, tumor spheroid formation, and angiogenic potential than AGS cells. CAGE exerted effects on the response to anticancer drugs and autophagic flux. CAGE was shown to bind to Beclin1, a mediator of autophagy. Overexpression of CAGE increased autophagic flux and invasion potential but inhibited the cleavage of PARP in response to anticancer drugs in CAGE CRISPR–Cas9 cell lines. TargetScan analysis was utilized to predict the binding of miR-302b-5p to the promoter sequences of CAGE, and the results show that miR-302b-5p directly regulated CAGE expression as illustrated by luciferase activity. MiR-302b-5p regulated autophagic flux and the response to anticancer drugs. CAGE was shown to bind the promoter sequences of miR-302b-5p. The culture medium of AGSR cells increased CAGE expression and autophagic flux in AGS cells. ImmunoEM showed CAGE was present in the exosomes of AGSR cells; exosomes of AGSR cells and human recombinant CAGE protein increased CAGE expression, autophagic flux, and resistance to anticancer drugs in AGS cells. MicroRNA array revealed miR-181b-5p as a potential negative regulator of CAGE. MiR-181b-5p inhibitor increased the expression of CAGE and autophagic flux in addition to preventing anticancer drugs from cleaving poly(ADP-ribose) polymerase (PARP) in AGS cells. TargetScan analysis predicted sphingosine 1-phosphate receptor 1 (SIPR1) as a potential target for miR-181b-5p. CAGE showed binding to the promoter sequences of S1PR1. The downregulation or inhibition of S1PR1 led to decreased autophagic flux but enhanced the sensitivity to anticancer drugs in AGSR cells. This study presents a novel role of the CAGE–miR-181b-5p–S1PR1 axis in anticancer drug resistance and autophagy.